PENGEMBANGAN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF UNTUK SISWA KELAS 3 SD PADA MATERI SEJARAH UANG MENGGUNAKAN ADOBE FLASH PROFESSIONAL CS6 - Efi Trianingrum; Gamaliel Septian Airlanda (FIP Unimed, 2017)
This study aims to develop IPS learning media in the form of interactive multimedia and test the feasibility of interactive multimedia learning media that has been developed. This type of research is research and development (R & D) which refers to the model developed by Borg and Gall. The results showed the feasibility of interactive multimedia aspects of the media of 4.00, material aspects of 3.23, and language aspects of 4.11. In a limited trial of student questionnaire results showed the feasibility of 4.34 and teacher questionnaires of 4.70. While the questionnaire results of students on a wide test show the feasibility of 4.44. Based on the result of a series of feasibility test process, interactive multimedia developed feasible to be used in IPS learning. Keywords: Development, Interactive Multimedia, IPS